2022
DOI: 10.1021/acs.biomac.2c00873
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Colon Cancer Treatment Using S100A9-Targeted Cowpea Mosaic Virus Nanoparticles

Abstract: Peritoneal metastases (PMs) occur due to the metastasis of gynecological and gastrointestinal cancers such as ovarian, colon, pancreatic, or gastric tumors. PM outgrowth is often fatal, and patients with PMs have a median survival of 6 months. Cowpea mosaic virus (CPMV) has been shown, when injected intratumorally, to act as an immunomodulator reversing the immunosuppressive tumor microenvironment, therefore turning cold tumors hot and priming systemic antitumor immunity. However, not all tumors are injectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…33,34 S100A9 is a widely studied biomarker in recent years and a pivotal mediator of cancer progression. [35][36][37] It is worth noting that clinical studies have found that downregulation of S100A9 expression in HCC can significantly inhibit cancer cell growth. 38 Therefore, targeting S100A9 is a possible strategy for HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 S100A9 is a widely studied biomarker in recent years and a pivotal mediator of cancer progression. [35][36][37] It is worth noting that clinical studies have found that downregulation of S100A9 expression in HCC can significantly inhibit cancer cell growth. 38 Therefore, targeting S100A9 is a possible strategy for HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…With ), and the CPMV capsid was modified with peptides to extend the ability of CPMV. 193 CPMV is a plant small ribonucleic acid virus that has been explored as an immunomodulatory agent for cancer therapy via in situ vaccination. The H6 and G3 used for modification bind to S100A9 molecules overexpressed in a variety of cancers including breast, ovarian, pancreatic, and gastric cancers for systemic administration of targeted therapies.…”
Section: Study On the Application Of Therapeutic Nanoagents In The Tr...mentioning
confidence: 99%
“…Copyright 2022, American Chemical Society. (b) Intratumoral injection of CPMV acts as an immunomodulator, reverses the immunosuppressive tumor microenvironment, warms up cold tumors, and induces systemic antitumor immunity . Reproduced from ref .…”
Section: Study On the Application Of Therapeutic Nanoagents In The Tr...mentioning
confidence: 99%
See 2 more Smart Citations